2001
DOI: 10.1002/jsfa.906
|View full text |Cite
|
Sign up to set email alerts
|

Sodium selenate fertilisation increases selenium accumulation and decreases glucosinolate concentration in rapid‐cycling Brassica oleracea

Abstract: Glucosinolates (GSs) are S-containing compounds found in Brassica species and whose degradation products may provide protection against cancer. Sulphoraphane, a product of 4-methylsulphinylbutyl GS degradation, is a particularly potent inhibitor of anticarcinogenic detoxi®cation enzymes. Selenium also has anticancer properties, and consumption of plants containing Se may be an effective way to increase dietary Se. Since plant uptake of Se and S is competitive, GS synthesis may be affected by Se fertilisation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 24 publications
11
59
1
Order By: Relevance
“…19 Charron et al reported a 90% reduction of SFN from 0.4 to 0.04 μmol/g after treatment of Brassica oleracea with 1 mg/L Na 2 SeO 4 , yielding a Se accumulation of 270.7 μg/g in shoots. 32 In our study, the selenium enrichment of broccoli was achieved by spraying 2 mg of selenate on one broccoli sprout, yielding 0.25 μg Se/g FW. The protocol for Se fortification applied in our study does not negatively affect glucosinolate concentrations 20 and does not, in turn, decrease glucoraphanin metabolites formed in vivo after dietary intake of the Se-fertilized broccoli.…”
Section: Article ' Results and Discussionmentioning
confidence: 99%
“…19 Charron et al reported a 90% reduction of SFN from 0.4 to 0.04 μmol/g after treatment of Brassica oleracea with 1 mg/L Na 2 SeO 4 , yielding a Se accumulation of 270.7 μg/g in shoots. 32 In our study, the selenium enrichment of broccoli was achieved by spraying 2 mg of selenate on one broccoli sprout, yielding 0.25 μg Se/g FW. The protocol for Se fortification applied in our study does not negatively affect glucosinolate concentrations 20 and does not, in turn, decrease glucoraphanin metabolites formed in vivo after dietary intake of the Se-fertilized broccoli.…”
Section: Article ' Results and Discussionmentioning
confidence: 99%
“…Se treatment at 100 μg Se/m concentration, however, contributed to the highest content of sulfur in broccoli heads. According to different studies, sulfate uptake increased in Brassica oleracea with the increase in Se concentrations in nutrient solutions (Kopsell and Randle, 1999;Charron et al, 2001;Toler et al, 2007). Toler et al (2007) demonstrated that S concentration of plants exposed to Se closely resembled those exposed to elevated S. On the other hand, selenate absorbs via sulfate carriers and then assimilates via the same enzymes used in S assimilation and can be incorporated into amino acids (De Souza et al, 1998).…”
Section: Mineral Elements Concentrationmentioning
confidence: 99%
“…In particular, SeMSC displays the highest anticarcinogenic activity, in mammals, of all seleno amino acids and methylseleno amino acids (Davis, Zeng, & Finley, 2002). However, Brassicaceae contains a naturally low SeMSC concentration, which can be significantly increased by fortifying the soil or culture media with sodium selenite or selenate (Charron, Kopsell, Randle, & Sams, 2001 addition, selenoglucosinolates have higher anticarcinogenic activity than thioglucosinolates in Se-treated broccoli (Matich et al, 2012). In plants, the chemical and physical resemblance between Se and S causes both elements to share common metabolic pathways in plants, thus, Se often substitutes for S in physiological and metabolic processes (Sors, Ellis, & Salt, 2005).…”
Section: Introductionmentioning
confidence: 99%